2002
DOI: 10.1183/09031936.02.00282402
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of matrix metalloproteinase‐8 and ‐9 in bronchiectatic airwaysin vivo

Abstract: The progressive bronchial dilatation in bronchiectasis is likely to be the result of continued airway matrix destruction, although little is known about the role of neutrophil matrix metalloproteinases (MMPs) in this process.Immunohistochemistry has been used to investigate the expression and cellular localisation of MMP-8 and MMP-9 in bronchiectatic airways in vivo. Endobronchial biopsies were taken from 25 bronchiectatic patients, and from the right lower lobe in 14 control subjects. MMP-8, MMP-9, neutrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 28 publications
1
71
0
1
Order By: Relevance
“…Currently, we know that chronic infection and inflammation in patients with CF is associated with progressive airways obstruction and bronchiectasis of the cartilaginous airways [1]. MMP2, 8 and 9 have been shown to be elevated in patients with bronchiectasis [65][66], but the processes and the specific cells involved in the destruction of airway cartilage and subsequent development of bronchiectasis are poorly understood. Based on the biological plausibility and current lack of explanation for the elevated MMPs and bronchiectasis in CF, it is tempting to speculate that IL-17 is a critical component in this process.…”
Section: Th 17 Cells and Cartilage Destruction Of The Joint: A Link Tmentioning
confidence: 99%
“…Currently, we know that chronic infection and inflammation in patients with CF is associated with progressive airways obstruction and bronchiectasis of the cartilaginous airways [1]. MMP2, 8 and 9 have been shown to be elevated in patients with bronchiectasis [65][66], but the processes and the specific cells involved in the destruction of airway cartilage and subsequent development of bronchiectasis are poorly understood. Based on the biological plausibility and current lack of explanation for the elevated MMPs and bronchiectasis in CF, it is tempting to speculate that IL-17 is a critical component in this process.…”
Section: Th 17 Cells and Cartilage Destruction Of The Joint: A Link Tmentioning
confidence: 99%
“…Increased levels of MMP-8 and MMP-9 have been reported in BAL fluid of subjects with bronchiectasis [103,104]. MMP-8 and MMP-9 expression in the bronchiectasis airways correlate significantly with airway neutrophil numbers but not with lung function and extension of disease [105].…”
Section: The Role Of Cells In Bronchiectasis Airway Inflammation Neutmentioning
confidence: 99%
“…Finally, MMP-8 levels in BALF also correlate with the severity of bronchiectasis, a disease characterized by a permanent dilation of the bronchi due to chronic inflammation, leading to irreparable deformation of bronchial wall components (Sepper et al, 1995). Other studies identified activated epithelial cells (as well as infiltrating neutrophils and macrophages) as the cell types responsible for the de novo MMP-8 expression in the course of this pathology (Prikk et al, 2001;Zheng et al, 2002).…”
Section: Neoplastic Diseasesmentioning
confidence: 99%